Synthesis and application of amine-containing conjugated small molecules for the automatic formation of an electron transporting layer via spontaneous phase separation from the bulk-heterojunction layer. Issue 55 (9th October 2019) - Kim, Juae; Kim, Yong Ryun; Kim, Minji; Jin, Jong Sung; Sung, Ji Yeong; Back, Hyungcheol; Kim, Heejoo; Lee, Kwanghee; Suh, Hongsuk
Abstract : Formation of a spontaneous self-assembled electron transporting layer. Abstract : Carbazole-based conjugated small molecule electrolytes (CSEs) containing different numbers of amine groups were synthesized and applied to bulk-heterojunction (BHJ) organic solar cells for the formation of a spontaneous self-assembled electron transporting layer (ETL). The active layer was spin-coated with a mixture solution containing the BHJ materials and a small amount of CSE, and a thin layer of CSE was formed underneath the active layer (CSE/BHJ bi-layer) via spontaneous phase separation, which is confirmed by the depth profile of the time of flight secondary ion mass spectroscopy (ToF-SIMS) spectrum. The amino groups in the CSEs form hydrogen-bonds with the surface of indium tin oxide (ITO), which acts as an ETL in BHJ solar cells. Moreover, the formed CSE layer is capable of changing the effective work function (WF) of ITO. An increasing number of amino groups in the CSEs (from Cz1N to Cz3N ) provides more reduction of the effective WF of ITO, which results in a lower internal resistance and a higher power conversion efficiency (PCE). Furthermore, the enhanced hydrogen bonding between the amines and ITO with an increased number of amine groups has been studied by XPS. This result suggests that one-step processing provides a reduction of the manufacturing cost, which can provide an attractive design concept for ETL fabrication.